Proton Pump Inhibitors and Serum Magnesium Levels in Patients With Torsades de Pointes - Lazzerini, Pietro E.; Bertolozzi, Iacopo; Finizola, Francesco; Acampa, Maurizio; Natale, Mariarita; Vanni, Francesca; Fulceri, Rosella; Gamberucci, Alessandra; Rossi, Marco; Giabbani, Beatrice; Caselli, Michele; Lamberti, Ilaria; et al. (Frontiers in Pharmacology, 2018)
Background: Torsades de pointes (TdP) is a life-threatening ventricular tachycardia occurring in long QT-syndrome patients. It usually develops when multiple QT-prolonging factors are concomitantly present, more frequently drugs and electrolyte imbalances. Since proton–pump inhibitors (PPIs)-associated hypomagnesemia is an increasingly recognized adverse event, PPIs were recently included in the list of drugs with conditional risk of TdP, despite only few cases of TdP in PPI users have been reported so far. Objectives: Aim of the present study is to evaluate whether PPI-induced hypomagnesemia actually has a significant clinical impact on the risk of TdP in the general population. Methods: Forty-eight unselected patients who experienced TdP were consecutively enrolled (2008-2017). Shortly after the first TdP episode, in those patients who did not receive magnesium sulfate and/or potassium or calcium replacement therapy, serum electrolytes were measured and their relationship with PPI usage analyzed. Results: Many patients (28/48, 58%) were under current PPI treatment when TdP occurred. Among TdP patients in whom serum electrolyte determinations were obtained before replacement therapy (27/48), those taking PPIs had significantly lower serum magnesium levels than those who did not. Hypomagnesemia occurred in ~40% of patients receiving PPIs (6/14), in all cases after an extended treatment (>2 weeks). In patients taking PPIs the mean QT-prolonging risk factor number was significantly higher than in those who did not, a difference which was mainly driven by lower magnesium levels. Conclusions: In unselected TdP patients, PPI-induced hypomagnesemia was common and significantly contributed to their cumulative arrhythmic risk. By providing clinical support to current recommendations, our data confirm that more awareness is needed when a PPI is prescribed, specifically as regards the risk of life-threatening arrhythmias.